2018
DOI: 10.1111/bph.14147
|View full text |Cite
|
Sign up to set email alerts
|

Single and combined effects of plant‐derived and synthetic cannabinoids on cognition and cannabinoid‐associated withdrawal signs in mice

Abstract: CBD as a monotherapy may prove to be a safer pharmacological agent, than CB receptor agonists alone or in combination with CBD, for the treatment of several disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…Preclinical data on THC prove anticonvulsant ( 22 ), as well as proconvulsive ( 23 ) and adverse effects on neurocognitive functioning ( 24 ). Clinical data show adverse structural and functional effects resulting from long term THC use ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical data on THC prove anticonvulsant ( 22 ), as well as proconvulsive ( 23 ) and adverse effects on neurocognitive functioning ( 24 ). Clinical data show adverse structural and functional effects resulting from long term THC use ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, in alcohol-and cocaine-dependent rats CBD attenuated the drug seeking behaviour without inducing tolerance, sedation, or interfering with normal motivated behaviour (Gonzalez-Cuevas et al, 2018). In rodents, CBD chronic administration did not induce dependence whilst the long-term co-administration of equal ratios of CBD and THC did not reduce THC dependence levels (Myers et al, 2018). In evaluating the role of oral CBD in frequent, healthy, cannabis users, Babalonis et al (2017) found that CBD at 200, 400, 800 mg once daily (OD) was not associated with abuse when compared to oral placebo and active marijuana products with high levels of THC up to 5.3-5.8%.…”
Section: Introductionmentioning
confidence: 94%
“…CB1R antagonist (SR141716) administration precipitated withdrawal signs in chronically THC-treated C57BL/6J mice and they were not attenuated by CBD. However, the lack of CBD-induced withdrawal signs or cognitive performance impairment, together with the robust anxiolytic effect led the authors to conclude that CBD as a monotherapy might be a safer pharmacological agent for the treatment of several disorders ( Myers et al, 2019 ).…”
Section: Cbd As a Potential New Pharmacological Tool For The Treatment Of Sudmentioning
confidence: 99%